Fixed wings UAV direction control “Hardware Design” - Khalil Abdallah, Mohamed; Hassan Abdalla Hashim, Aisha; Gasmalla, Tahani AbdallahAttia; Babiker, Sharief (IJCSNS, 2015)
The goal is to design of Unmanned Aerial Vehicle "UAV" system through the control of a stable fixed-wing aircraft to accomplish inexpensive, simple, and still efficient aircrafts by adding an inertial circuitry to the airplane that consists of a GPS unit, a microcontroller unit, and other devices. The aircraft has the ability to navigate from one place to another predefined place. Additional feature is to switch between two the modes of control: autopilot and manual is provided. In autopilot mode the aircraft is fully controlled by an on-board microcontroller, the only data needed for navigation is to specify the target waypoint, and then the system will navigate fully automatic towards the target until it reaches the target and does the specified duty.